Community participatory design in the information systems development process in Africa: a systemic literature review - Mutenda , Tapfumaneyi (Department of Information Systems, 2015)
Participatory design (PO) pertains to the different ways of incorporating ideas and acts of organisational members in designing, developing and evaluating an Information Systems (IS) artefact. The context of this study is community organisations in African settings participating in the designing and developing of an IS artefact. The study traces and synthesises findings from 95 articles on community PO in Information Systems Development in Africa. It argues that community PO consists of vast diverse constructs and implementations. This produced and reproduced concept is formulated in five major themes of: conceptualisations; ethics; standards; checks and balances and approaches; and perspectives and methodologies of PD. The themes constitute the possible ways of classifying PO research and practice in African settings. The results demonstrate that there is a wide belief that participation is one of the vital ingredients necessary for successful designing of IS artefacts for human development. However, the different elements involved in PO involve much discussion on what is known and needs to be known about PO and how to achieve the desired results by PD. The study uses Critical Research philosophy to pay special attention to the behavioural and attitudinal arguments of the different PO practices on community organisations. The researcher found Design Science (OS) principles that centre on devising an artefact as appropriate to frame this work. In sum, through the use of Critical Research and a OS lens, the researcher found that community participation is important in designing a useful IS artefact, but treacherous if misunderstood and inappropriately implemented.